Single-cell transcriptome analysis profiles cellular dynamics and transcriptional changes in diabetic wound tissues following ESWT treatment - Li, Dongyu; Wang, Yu; Wang, Yunlong; Sihao, Changhai; Wang, Lei; Xin, Shijie; Ma, Yuewen (Frontiers in Physiology, 2025)
IntroductionDiabetic wounds (DWs) remain a major complication of diabetes mellitus, characterized by impaired healing and limited therapeutic options. Extracorporeal shock wave therapy (ESWT), a non-invasive physical modality, has recently shown promise in accelerating chronic wound repair, yet the underlying cellular mechanisms remain poorly understood.MethodsHere, we employed single-cell RNA sequencing (scRNA-seq) to construct a comprehensive cellular atlas of DW tissues treated with ESWT, profiling approximately 39,475 cells.ResultsOur analysis identified 12 major cell populations, including macrophages, fibroblasts, endothelial cells, keratinocytes, and immune subsets, and revealed widespread transcriptional reprogramming associated with ESWT treatment. ESWT promoted the expansion of reparative macrophages, activated proregenerative fibroblast states, and restored angiogenic programs in endothelial cells. Moreover, cell–cell communication analysis revealed that ESWT not only attenuates pro-inflammatory signaling but also activates immune cell communication networks, thereby enhancing T cell, NK cell, and dendritic cell interactions. These changes collectively promote immune regulation and tissue repair, contributing to the restoration of a balanced wound microenvironment.DiscussionTogether, these findings provide a high-resolution single-cell map of ESWT mediated cellular and molecular alterations in DWs and uncover key cellular pathways contributing to improved tissue repair. This study offers new insights into the mechanisms of ESWT and supports its translational potential as a therapeutic strategy for chronic wound management.